Penerapan Model SDLC Terhadap Sistem Informasi Penjualan Dan Persediaan Bangunan Pada CV. Nilafa - Romindo, Romindo
Sales is an important thing to pay attention to in a business because through sales the business can make a profit. Sales are also very closely related to inventory, because without inventory the sales process cannot take place. However, the recording of inventory and sales on CV. Nilafa is always handmade so it takes a long time and mistakes are not uncommon. Therefore, a research was conducted in designing a web-based inventory and sales information system using the Software Development Life Cycle (SDLC) methodology. This system is designed using ASP.NET and C# programming languages, as well as SQL Server for database purposes. This sales and inventory information system can help companies quickly find out the amount of inventory, record incoming and outgoing goods, store customer data, reduce the risk of errors or omissions, especially those caused by human error, to make reports quickly and easily. and can be filtered based on user wishes, as well as estimates of the best-selling items so that it can be estimated which items will be purchased/re-supplied through the created information system.